2010
DOI: 10.1186/1471-2407-10-176
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of archived DNA microarrays identifies genes regulated by hypoxia and involved in a metastatic phenotype in cancer cells

Abstract: BackgroundMetastasis is a major cancer-related cause of death. Recent studies have described metastasis pathways. However, the exact contribution of each pathway remains unclear. Another key feature of a tumor is the presence of hypoxic areas caused by a lack of oxygen at the center of the tumor. Hypoxia leads to the expression of pro-metastatic genes as well as the repression of anti-metastatic genes. As many Affymetrix datasets about metastasis and hypoxia are publicly available and not fully exploited, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…These pathways are "toll-like receptor signaling pathway", "fMLP induced chemokine gene expression in HMC-1 cells", "T cell receptor signaling pathway", "Fc epsilon RI signaling pathway" and "Fc gamma R-mediated phagocytosis". The first four were already discussed previously in Pierre et al [15]. However, the Fc gamma R-mediated phagocytosis pathway was not.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…These pathways are "toll-like receptor signaling pathway", "fMLP induced chemokine gene expression in HMC-1 cells", "T cell receptor signaling pathway", "Fc epsilon RI signaling pathway" and "Fc gamma R-mediated phagocytosis". The first four were already discussed previously in Pierre et al [15]. However, the Fc gamma R-mediated phagocytosis pathway was not.…”
Section: Discussionmentioning
confidence: 86%
“…To obtain n, we multiplied this number by two to take into account the genes involved in metastasis and/or hypoxia still not demonstrated as such. The choice of multiplier was motivated by our observation in a previous work about cancer using a meta-analysis methodology in which we retrieved 183 genes of interest, among which 99 were already known to be involved in cancer [15]. This showed that the number of genes known to be involved in a cancer-related phenomenon can be multiplied by two to take into account those genes still not known to be involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that researchers use these data to address questions far beyond those for which the original studies were designed to address. Examples include using GEO data to test new algorithms (18), functionally characterize genes (19), create new added-value targeted databases (20), perform massive meta-analyses across thousands of independently-generated assays (21), and identify diagnostic protein biomarkers for disease (22). …”
Section: Discussionmentioning
confidence: 99%